Efficient polymer solar cells based on the synergy effect of a novel non-conjugated small-molecule electrolyte and polar solvent. Issue 7 (26th January 2016) - Liu, Zhiyang; Ouyang, Xinhua; Peng, Ruixiang; Bai, Yongqi; Mi, Dongbo; Jiang, Weigang; Facchetti, Antonio; Ge, Ziyi
Abstract : The power conversion efficiencies of polymer solar cells were largely improved by introducing a non-conjugated small-molecule electrolyte as a cathode interlayer. Abstract : A novel non-conjugated small-molecule electrolyte was invented as a cathode interlayer in PTB7:PC71 BM-based polymer solar cells (PSCs). We discovered a significant synergy effect for improving the device efficiency between methanol treatment and the interlayer. The methanol treatment mainly contributed to the open-circuit voltage, while the interlayer primarily enhanced the short-circuit current and fill factor. Under the effective synergy effect, power conversion efficiencies (PCEs) of PTB7:PC71 BM-based PSCs were largely improved from 3.89% to 9.79% for conventional PSCs and from 7.34% to 9.10% for inverted PSCs. Our findings create a new path of interfacial modification for highly efficient PSCs.